An Optimized and General Synthetic Strategy To Prepare Arylnaphthalene Lactone Natural Products from Cyanophthalides. Issue 13 (4th April 2017) - Kim, Taejung; Jeong, Kyu Hyuk; Kang, Ki Sung; Nakata, Masaya; Ham, Jungyeob
Abstract : A simple method for the preparation of arylnaphthalene lactone natural products was developed and used to synthesize diphyllin (10 ), justicidin A (12 ), cilinaphthalide B (13 ), taiwanin E (15 ), chinensinaphthol (16 ), taiwanin E methyl ether (17 ), chinensinaphthol methyl ether (18 ), justicidin C (21 ), and justicidin D (22 ). Key steps of the syntheses include the Hauser–Kraus annulation of cyanophthalides7a and7b and Suzuki–Miyaura cross‐coupling reactions between arylnaphthalene lactones that contain a sulfonate group (i.e., 9, 14, 19, and20 ) and various potassium aryltrifluoroborates. Abstract : A simple method for the preparation of nine arylnaphthalene lactone natural products was developed. Key steps of the syntheses include the Hauser–Kraus annulation reaction of a cyanophthalide and a Suzuki–Miyaura cross‐coupling reaction between an arylnaphthalene lactone that contains a sulfonate group and a potassium aryltrifluoroborate.